Reading Habits and Comprehension: A Study of University Students - Rendi; Yeni Rahmawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Understanding information from a foreign language especially English is crucial for foreign language learners. One of the ways to understand the information is by active reading comprehension. Reading comprehension and reading habits are two elements of learning a language. Reading comprehension is the basic skill that is completed by the other skills. The goal of this research is to determine the relationship between students' reading habits and students' ability in reading comprehension in the second semester at Muhammadiyah University of East Kalimantan. In this quantitative research with correlational research, the researcher applied questionnaires to assemble the data. The questionnaire measures students' reading habits and the test measures students' reading comprehension. Based on the statistical data, the population would be around 2,362 students, and the sampling technique that would be used is a simple random sampling technique. Based on the table size sample, with a margin of error of 5%, it is gained that the total sample would be 330 students. The result of the study was the positive and medium relationship between these variables namely reading comprehension and reading habits. This research hopefully can be one of the references for identifying the literacy level of university students particularly in reading English texts